Perbandingan Pengaturan Restorative Justice Dalam Hukum Pidana Indonesia Dan Negara Kanada - Muhammad Fadhel Febriansyah (Jurnal Kajian Hukum Dan Kebijakan Publik | E-ISSN : 3031-8882, 2025)
Restorative Justice is an alternative paradigm in the criminal system in various countries, Indonesia and Canada are included in the list of countries that use restorative justice. This study aims to analyze and compare restorative justice arrangements in Indonesia and Canada, in order to understand how the two countries use and apply restorative justice principles. The legal issues that will be studied include the effectiveness of implementing this system to reduce the level of recidivism (relapse of a person's criminal behavior) and legal certainty for the parties involved. The method used is normative legal research with a comparative legal approach, and the legal materials used are legal literature, legislation, and academic journals. Then the results of this research show that Canada has already used restorative justice in its laws. Meanwhile in Indonesia, restorative justice is currently in the development stage with several policies that have not yet been fully integrated. So these findings show that there is a great need to strengthen policies and legal instruments in implementing restorative justice in Indonesia